Expanding the fetal phenotype: Prenatal sonographic findings and perinatal outcomes in a cohort of patients with a confirmed 22q11.2 deletion syndrome. Issue 8 (28th July 2018) - Schindewolf, Erica; Khalek, Nahla; Johnson, Mark P.; Gebb, Juliana; Coleman, Beverly; Crowley, Terrence Blaine; Zackai, Elaine H.; McDonald‐McGinn, Donna M.; Moldenhauer, Julie S.
Abstract : 22q deletion syndrome (22q11.2DS) is most often correlated prenatally with congenital heart disease and or cleft palate. The extracardiac fetal phenotype associated with 22q11.2DS is not well described. We sought to review both the fetal cardiac and extracardiac findings associated with a cohort of cases ascertained prenatally, confirmed or suspected to have 22q11.2DS, born and cared for in one center. A retrospective chart review was performed on a total of 42 cases with confirmed 22q11.2DS to obtain prenatal findings, perinatal outcomes and diagnostic confirmation. The diagnosis was confirmed prenatally in 67% (28/42) and postnatally in 33% (14/42). The majority (81%) were associated with the standard LCR22A‐LCR22D deletion. 95% (40/42) of fetuses were prenatally diagnosed with congenital heart disease. Extracardiac findings were noted in 90% (38/42) of cases. Additional findings involved the central nervous system (38%), gastrointestinal (14%), genitourinary (16.6%), pulmonary (7%), skeletal (19%), facial dysmorphism (21%), small/hypoplastic thymus (26%), and polyhydramnios (30%). One patient was diagnosed prenatally with a bilateral cleft lip and cleft palate. No fetus was diagnosed with intrauterine growth restriction. The average gestational age at delivery was 38 weeks and average birth weight was 3, 105 grams. Sixty‐two percentage were delivered vaginally and there were no fetal demises. A diagnosis of 22q11.2 deletion syndrome should be considered in all cases of prenatally diagnosed congenital heart disease, particularly when it is not isolated. Microarray is warranted in all cases of structural abnormalities diagnosed prenatally. Prenatal diagnosis of 22q11.2 syndrome can be used to counsel expectant parents regarding pregnancy outcome and guide neonatal management.